The Development of the Insect Puppet Storybook as a Means of Instilling Character Values in Thematic Learning at SD N 1 Sawangan: Pengembangan Buku Cerita Wayang Serangga Sebagai Sarana Penanaman Nilai Karakter pada Pembelajaran Tematik di SD N 1 Sawangan - Fauziah Dwi Rohmawati (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to develop an illustrated storybook featuring Wayang Serangga for thematic learning among elementary school students.  This study uses a development method by adapting the Borg and Gall development model. The development stages carried out include needs analysis, development design, creation of the initial prototype, evaluation, and production. Data analysis was conducted using product feasibility testing based on evaluation results, which covered several important aspects: material expert validation, media expert validation, trial results with target users, and expert assessment of the students’ work. Each of these aspects plays a role in assessing the extent to which the developed product meets quality and effectiveness standards for use in the learning context. The book was evaluated as "highly feasible" by content experts with a score of 91.0%, and by media experts with a score of 84.1%. Implementation of the storybook among fifth-grade elementary students yielded a "very good" response to the media at 98.7%, a "very good" level of material comprehension at 90.7%, and a "very good" level of character values comprehension at 81.2%. The students' project outcomes were categorized as 15% "less good," 40% "good," and 45% "very good." Based on these results, the illustrated storybook featuring wayang serangga is considered appropriate for use in thematic learning for fifth-grade elementary students.